Aggressive Behavior of Students with Hearing Impairment and Academic Engagement: A Study in South Punjab, Pakistan - Kubra, 1Khadija Tul; Warsi, Lubna Quddus; Sanam, Areba (Journal of Development and Social Sciences, 2024)
This study investigates the impact of aggressive behavior and influence of various forms (physical, verbal, and social) on academic engagement among students with hearing impairments in South Punjab, Pakistan.to address the research gap the study seek to develop effective intervention and support systems to enhance their educational experience. Aggressive behavior is one of the challenge faces by the student suffering with hearing impairments, which can significantly impact their academic engagement. The research uses a descriptive framework and survey approach to gather quantitative data focusing on special education schools in Multan, Bahawalpur, and DG Khan from teachers working with hearing-impaired students. The analysis, conducted using SPSS, aims to understand the prevalence of aggressive behavior and its effects on students' academic involvement. The findings are expected to inform interventions and support system that enhance the educational system of students with hearing impairments.